2016
DOI: 10.1111/ane.12553
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlates of memory complaints during AED treatment

Abstract: Objectives: To investigate clinical correlates of memory complaints (MC) during antiepileptic drug (AEDs) treatment in adults with epilepsy with special attention to the role of depression, using userfriendly standardised clinical instruments which can be adopted in any outpatient setting. Materials & methods:Data from a consecutive sample of adult outpatients with epilepsy assessed with the Neurological Disorder Depression Inventory for Epilepsy (NDDIE), the Adverse Event Profile (AEP) and the Emotional Therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The problem of neuropsychological deficits in adult-onset epilepsies is quite complex. Several studies have clearly shown that subjective memory complaints do not correlate with formal neuropsychological deficits but are rather due to other factors, especially anxiety and depression (31,32). Antiepileptic drugs have a different propensity for cognitive side effects but a number of different variables, which are both patient-related and epilepsy-related, have to be taken into account in adults (30).…”
Section: Cognitive Problemsmentioning
confidence: 99%
“…The problem of neuropsychological deficits in adult-onset epilepsies is quite complex. Several studies have clearly shown that subjective memory complaints do not correlate with formal neuropsychological deficits but are rather due to other factors, especially anxiety and depression (31,32). Antiepileptic drugs have a different propensity for cognitive side effects but a number of different variables, which are both patient-related and epilepsy-related, have to be taken into account in adults (30).…”
Section: Cognitive Problemsmentioning
confidence: 99%
“…A high level of anxiety is also associated with perceived stigma in persons with newly diagnosed epilepsy (Lee et al, 2015). Anxiety also contributes to memory complaints in persons with epilepsy (Mula et al, 2016).…”
Section: Impact Quality-of-lifementioning
confidence: 99%
“…Finally, a number of studies are now pointing out that depression is a prognostic marker in epilepsy as it is associated not only with poor quality of life [16] but also with antiepileptic drug-resistance [17,18], increased seizure severity [19], increased side effects of antiepileptic drugs [20], increased risk of accident and injuries [21], poor outcome after epilepsy surgery [22] and increased mortality [23].…”
Section: Introductionmentioning
confidence: 99%